Mobile emergency alerting made accessible. (8th March 2010) - Johnson, Jeremy; Mitchell, Helena; LaForce, Salimah; Price, Ed; , Frank Lucia
It is critical that next-generation warning systems be developed such that persons with disabilities are given equal access to emergency alerts. This paper discusses research and development activities to provide next-generation, mobile emergency alerting systems to people with disabilities. A framework for prototyping mobile phone-based emergency alert systems and multiple systems built on this framework are presented. Results from field trials indicated support and the need for accessible emergency alert/notification features. The paper concludes that simple accommodations can be made to services and software on mobile devices that greatly increase the accessibility of mobile emergency alerts to persons with disabilities.